2019
DOI: 10.1016/j.heliyon.2019.e02631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Ornithine application on improving drought tolerance in sugar beet plants

Abstract: The objective of this research was to determine the foliar application of L-ornithine (0.0, 0.30 and 0.60 mM) as a precursor of polyamines, at vegetative stage was on antioxidant defense and growth of drought stressed sugar beet plants grown under clay and sandy soil conditions. Two water irrigation treatments (80% and 40% Field capacity) were carried out on sugar beet plants grown in pots under greenhouse conditions. Water stress resulted in significantly decrement in growth parameters including root diameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 31 publications
3
33
0
Order By: Relevance
“…Capability of germination and seedling growth [17,22,25,30,38] Decline in the root weight and root length Higher root/shoot ratio Decline in the root weight and root length Higher root growth [8,34,38,61] Low water content and small leaf area The initial eight-weeks of growth associated with seedling vigor in sugar beet is considered to be the most crucial stage [79], which determines field emergence and stand establishment. Salt and drought stress negatively affect germination and seedling development in sugar beet [4,80] by affecting ionic balance, resulting in hyperosmotic stress and oxidative damage [25,70,81].…”
Section: Capability Of Germination and Seedling Growthmentioning
confidence: 99%
See 2 more Smart Citations
“…Capability of germination and seedling growth [17,22,25,30,38] Decline in the root weight and root length Higher root/shoot ratio Decline in the root weight and root length Higher root growth [8,34,38,61] Low water content and small leaf area The initial eight-weeks of growth associated with seedling vigor in sugar beet is considered to be the most crucial stage [79], which determines field emergence and stand establishment. Salt and drought stress negatively affect germination and seedling development in sugar beet [4,80] by affecting ionic balance, resulting in hyperosmotic stress and oxidative damage [25,70,81].…”
Section: Capability Of Germination and Seedling Growthmentioning
confidence: 99%
“…In addition to salt stress, low soil moisture contents at critical developmental stages such as field emergence and initial seedling establishment could be also detrimental for sugar beet growth [87]. Occurrence of drought stress at vegetative phase can dampen the root and shoot fresh weights and root diameter of sugar beet [8], suggesting that the yield reduction due to drought stress is reciprocated with plant developmental stage as well as severity of water limitation [88]. In a recent work, Skonieczek et al (2018) identified three sugar beet cultivars, which can sustain low moisture at the emergence stage [89].…”
Section: Capability Of Germination and Seedling Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled foliar application of Put can trigger physiological processes and induce osmotic adjustment molecules like proline, total soluble sugars and amino acids in plants [ 35 ]. The role of PAs in the biosynthesis of DNA, RNA, and protein, maintaining plant growth and development, lingering ageing, and protecting the membrane from oxidative damage by removing free radicals in plants were also reported [ 37 ]. Earlier, exogenous Put was reported enhanced salt tolerance by accumulating higher osmolytes, regulating carbon fixation, electron transport, energy and defence pathways in Cynodon dactylon [ 38 ]; eliminating reactive oxygen species in Citrus aurantium [ 39 ]; regulation of photosynthetic pathways in Citrus reticulata × Citrus limetta [ 40 ]; photosynthetic [ 41 ] and root growth [ 4 ] associated proteins in Cucumis sativa .…”
Section: Introductionmentioning
confidence: 99%
“…The yield of sugar beet largely depends on the size of the leaf rosette, its photosynthetic activity, the ability to accumulate and lay assimilates in root crops, and also withstand various kinds of stress [3,4,5]. The growth of the leaf apparatus and root crops during the growing season occurs unevenly.…”
Section: Resultsmentioning
confidence: 99%